Surgery for Anomalous Aortic Origin of a Coronary Artery (AAOCA) in Children and Adolescents: A Meta-Analysis. Issue 4 (July 2022) - Ponzoni, Matteo; Frigo, Anna C.; Padalino, Massimo A.
We conducted a systematic review and meta-analysis of the literature to assess the outcomes of surgery for the anomalous aortic origin of a coronary artery in children and young adults (<30 years). Thirteen publications were selected, including a total of 384 patients. Unroofing of the intramural segment was adopted in 92% (95% CI: 81%-98%) of cases, with pooled early and late mortality of 0% (95% CI: 0%-0.3%) and 0.1% (95% CI: 0%-1%), respectively. Reoperation for aortic regurgitation was anecdotal. Surgical management of anomalous aortic origin of coronary arteries can be achieved with excellent results in pediatric patients, but concerns remain about the durability of surgery.